Dynamical lymphadenectomy as a component of multidisciplinary approach while doing operative interventions for pancreatic cancer - O. Yu. Usenko; M. Yu. Nychytailo; M. S. Zagriichuk; V. V. Kropelnytskyi; N. E. Klochkova; Yu. V. Nezhentseva; Ya V. Romaniv; O. O. Pidopryhora; D. M. Skrypka (Клінічна хірургія)
Objective. To improve the results of treatment of pancreatic cancer, using modification of volumes of lymphadenectomy and application of multidisciplinary approach.